The Implementation of Web-Based Financial Statements Application in Islamic Education Foundations - Iwan Suhasto; Shinta Anggraeny; Dewi Kirowati (Jurnal AKSI (Akuntansi dan Sistem Informasi), 2021)
Islamic Education Foundation is a non-profit entity consisting of MA, MTs, Vocational Schools, Foundations, and Islamic Boarding Schools. This study aims for a web application that can be used in the financial data processing of the Al-Mujaddadiyyah Islamic Education Foundation replacing manually. The application is designed using the waterfall development method. The application was tested on several browsers and tested by the foundation consisting of the chairman of the foundation, the MTs admin, the MA admin, and the SMK admin. This application makes it easy in the process of reporting financial statements. The features contained in the application include administration management, donations, financial reports, student data, and employee data. Financial statements are divided into statements of financial position, activity reports, and cash flow statements.